Ultrashort Beryllium−Beryllium Distances Rivalling Those of Metal−Metal Quintuple Bonds Between Transition Metals. Issue 50 (16th November 2016) - Yuan, Caixia; Zhao, Xue‐Feng; Wu, Yan‐Bo; Wang, Xiaotai
Abstract: Chemical bonding is at the heart of chemistry. Recent work on high bond orders between homonuclear transition metal atoms has led to ultrashort metal−metal (TM−TM) distances defined as d M−M <1.900 Å. The present work is a computational design and characterization of novel main group species containing ultrashort metal−metal distances (1.728–1.866 Å) between two beryllium atoms in different molecular environments, including a rhombic Be2 X2 (X=C, N) core, a vertical Be−Be axis in a 3D molecular star, and a horizontal Be−Be axis supported by N‐heterocyclic carbene (NHC) ligands. The ultrashort Be−Be distances are achieved by affixing bridging atoms to attract the beryllium atoms electrostatically or covalently. Among these species are five global minima and one chemically viable diberyllium complex, which provide potential targets for experimental realization. Abstract : Short and sweet : High level ab initio calculations indicate that, with the aid of bridging atoms and supporting ligands, ultrashort Be−Be distances (1.728–1.866 Å) can be achieved that match the quintuple bond distances between two 3d transition metal atoms. Stability analyses suggest that the majority of these beryllium species are potential targets for experimental realization.